"Disease" of the Nation, Family and Individual: Three Moral Discourses of Alcohol Problems in Finnish Women's Magazines from the 1960s to the 2000s. (21st March 2015) - Törrönen, Jukka; Simonen, Jenni; Tigerstedt, Christoffer
Abstract : Women's magazines can be seen as a genre that form feminized public spaces where everyday life contradictions of women's life are negotiated. The study examines the ways in which Finnish women's magazines have dealt with alcohol problems. The data covers six primary sampling years: 1968, 1976, 1984, 1992, 2000 and 2008. The data is analyzed by drawing on the concept of 'moral regulation'. The analysis shows that a family-centered framing dominated the constructions of alcohol problem: fathers' and husbands' alcoholism appeared as a main object of regulation in all decades under study, while mothers' and wives' alcoholism was much less prevalent.